Appplication of CFD for 1,2- dichloroethane production by ethylene oxychlorination in fluidized bed reactor - Kodchakong, Anorna; Srinophakun, Thongchai (Engineering and Applied Science Research, 2015)
A computational fluid dynamics simulation, CFD, of ethylene oxychlorination for the production of 1,2-dichoroethane in a fluidized-bed reactor is developed in this research. This CFD model bases on two-phase flow model that is used to perform the high resolution of three-dimension numerical simulations of gas-solid in a fluidized bed, The results can be shown as the profile of temperature and parameters distribution. In the study of ethylene mole fraction from 0.227 to 0.356 with constant ratio of hydrochloric acid to oxygen at 3.6. the optimum operating condition for a maximum ethylene conversion is found at mole ti'action of ethylene equal to 0.34. The behavior of fluid in the operating temperature and ethylene conversion gradually increase according to the increase of cooling coils temperature from 300 to 450 K. The maximum ethylene conversion. 95%. occurred at cooling coils temperature of 450 K.